Analytical and Numerical Model of Low DOF Manipulators. (2015) - Forgó, Zoltán; Tolvaly-Roşca, Ferenc
Abstract: The paper introduces the use of a novel drive module with one translational and one rotational degree of freedom. The mechanism of the presented system has a timing belt setup, which enables a parallel drive of two DOF. Based on this mechanism the possibilities to build a low (2, 3 and 4) DOF manipulator are systematic presented, followed by the mathematical models for the geometry and kinematics. The advantages of the new mechanisms are underlined by presenting numerical results.